Madurez sexual, Índice de condición y rendimiento de Pinctada mazatlanica (Pterioida: Pteriidae), Golfo de Nicoya, Costa Rica - Solano López, Yonohide; Cabrera Peña, Jorge; Palacios, José A; Cruz, Rafael A (Revista de Biología Tropical, 1997)
The reproductive cycle, condition index and meat yield of 627 specimens of pearl oyster, Pinctada mazatlanica were studied in Isla Pan de Azúcar, Golfo de Nicoya, Costa Rica from September 1993 through September 1994. Sexual maturity was determinated by a smear method and macroscopic observation of gonads. The sexes are separated and there is no sexual dimorphism. however, the gonadal tissue changes in consistency and color. The percentage of males and females was approximately 1.6: 1 (range 0.8: 1 to 4.5: 1). Throughout the study period individuals of unknown sex were found, with a mean of 6.60 ±2.90 % (range 4.2 to 13.2 %). The minimum shell height at sexual maturity was 45 mm for males and females. The mean condition index was 18.92 ± 4.4 %. The condition index appropriately reflected the gonadic development. Mean population meat yield was 13.89 ± 3.7 % (range 14.13 to 29.1 %). Mature individuals occur yearround with two peaks of spawning activity observed in October 1993 and June 1994.